Cervical leiomyomas: a surgeon’s challenge - C., Pushpa; Ashok R. Anand; Aditi R. Jain (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Leiomyoma are benign uterine tumors of unknown etiology. Only 5% of the cases are cervical and are usually single. Extraperitoneal leiomyomas leads to pressure symptoms. They may be submucosal, intramural or sub-serosal type. Anterior cervical fibroids are the most common. Central cervical fibroids are described as “The Lantern on the dome of St. Paul’s”. A retrospective clinical study of 6 cervical fibroids operated in the department of Obstetrics and Gynecology, in a tertiary care hospital in Mumbai for a period of 24 months from March 2021 to February 2022. Patients were studied with respect to clinical profiles, pre-operative investigations, intra- operative surgical challenges and post-operative surveillance. In our study we observed that cervical fibroids were most commonly diagnosed in the age group of 40-50 years, and most commonly in women of second parity. The most common presenting symptom was pain in abdomen. All patients underwent hysterectomy (abdominal or vaginal), wherein 16% of them required blood transfusion. The largest cervical fibroid operated was 20 x 12 x 10 cm in size with uterus corresponding to 22 weeks of gestation. Excision of cervical fibroids is a challenging procedure due to its close proximity to ureters. It is only with experience and with fine surgical skills that a good patient outcome can be achieved. Even after advent of various alternative management options, surgery remains the mainstay of treatment and is still a surgeon’s nightmare.